Digital and Technology Literacy Training for Youth in Latimojong Village, Baraka District, Enrekang Regency - Hasman, Hasman; Amri, Amri (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This training was attended by 30 young people from Latimojong Village with diverse educational backgrounds and professions. The results achieved from this training include. Improvement in Digital Literacy: About 85% of the participants demonstrated a significant increase in their understanding of basic digital technology and its use. Young people who were previously unfamiliar with the internet are now able to search for information and use social media for productive purposes. (2). Development of Practical Skills: The training participants have mastered basic ICT skills, such as operating office software, creating digital content, and using other productivity applications. Some participants have even started developing local content to promote through social media and blogs. (3) Awareness of Digital Security: The training also successfully increased awareness of the importance of protecting personal data and ethics in internet use. Participants now understand digital security risks, such as online fraud, and have been trained to safeguard their personal data After the training, participants received support and mentoring from the facilitator team to ensure the application of the materials learned. The facilitator team provided guidance in developing small digital-based projects, such as creating a village blog or an application for promoting local products.